Movimentos LGBTQIA+: um estudo do reconhecimento da união homoafetiva à luz da demodiversidade. - Vignoli, Igor Felipe Araújo Nascimento (2023)
This dissertation addresses the ideal of demodiversity that seeks to understand democratic reality based on respect and recognition of the diversities existing in society. The object of study are the LGBTQIA+ movements (Lesbian, Gay, Bisexual, Transsexual, Transvestite, Transgender, Queer, Intersex, Agender and others far from the hegemonic standard), with the purpose of answering the starting question: what are the contributions of the LGBTQIA+ movements? in the judgment that recognized same-sex unions in the STF in ADPF 132 and ADI 4277? This study is justified by the fact that in 2011, in a historic judgment, the Supreme Court recognized same-sex unions along the same lines as stable unions, this being a real change in the hegemonic standards of society. Furthermore, it studies the importance of LGBTQIA+ movements as promoters of new concepts and experiences, in order to understand the “other” as a fundamental part in society for the achievement of demodiversity, demystifying concepts and standards that stigmatize or make LGBTQIA+ people vulnerable and that have repercussions on absences or omissions in the implementation and guarantee of rights. The research adopts the principles of legal doctrine and dogmatics, seeking to understand the ways in which the LGBTQIA+ movements influenced the decision. As a methodology, a legal analysis was carried out with triangulation between jurisprudence (ADPF 132 and ADI 4277), doctrine and dogmatics. Boaventura de Sousa Santos, Nancy Fraser, Maria Berenice Dias, Maria da Glória Gohn, Renan Quinalha and João Silvério Trevisan are some of the authors who are in the theoretical framework of the dissertation. Finally, the dissertation seeks to contribute to studies on demodiversity and the role of LGBTQIA+ movements as social transformers, given the history of violation and oppression directed at this population.